Investigation of the Effect of PbO Doping on Telluride Glass Ceramics as a Potential Material for Gamma Radiation Shielding - Kozlovskiy, Artem L.; Shlimas, Dmitriy I.; Zdorovets, Maxim V.; Elsts, Edgars; Konuhova, Marina; Popov, Anatoli I. (MDPI, 2023)
The purpose of this paper is to study the effect of PbO doping of multicomponent composite glass-like ceramics based on TeO2, WO3, Bi2O3, MoO3, and SiO2, which are one of the promising materials for gamma radiation shielding. According to X-ray diffraction data, it was found that the PbO dopant concentration increase from 0.10 to 0.20–0.25 mol results in the initialization of the phase transformation and structural ordering processes, which are expressed in the formation of SiO2 and PbWO4 phases, and the crystallinity degree growth. An analysis of the optical properties showed that a change in the ratio of the contributions of the amorphous and ordered fractions leads to the optical density increase and the band gap alteration, as well as a variation in the optical characteristics. During the study of the strength and mechanical properties of the synthesized ceramics, depending on the dopant concentration, it was found that when inclusions in the form of PbWO4 are formed in the structure, the strength characteristics increase by 70–80% compared to the initial data, which indicates the doping efficiency and a rise in the mechanical strength of ceramics to external influences. During evaluation of the shielding protective characteristics of the synthesized ceramics, it was revealed that the formation of PbWO4 in the structure results in a rise in the high-energy gamma ray absorption efficiency. © 2023 by the authors.--//-- This is an open access article Kozlovskiy A.L., Shlimas D.I., Zdorovets M.V., Elsts E., Konuhova M., Popov A.I.; Investigation of the Effect of PbO Doping on Telluride Glass Ceramics as a Potential Material for Gamma Radiation Shielding (2023) Materials, 16 (6), art. no. 2366; DOI: 10.3390/ma16062366; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85152065176&doi=10.3390%2fma16062366&partnerID=40&md5=34067687ddfd88cbc2bd3e23cbedeb27 published under the CC BY 4.0 licence.
This research was funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (No. BR11765580). In addition, A.I.P. thanks the Institute of Solid-State Physics, University of Latvia. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES; absorption; doping; optical properties; protective materials; shielding materials